Role of organic acids in phosphate mobilization from iron oxide - Johnson, Sarah E.; Loeppert, Richard H. (Wiley, 2006)
Phosphate deficiency often limits crop production in acid tropical soils because of the strong bonding of phosphate by Fe and Al oxides. Organic‐acid exudation from roots is one reported plant adaptation to P deficiency. The objective of this study was to predict the efficacy of this P‐deficiency stress response in different soil types by investigating the mechanism of organic‐acid‐induced P mobilization from different oxide minerals. Greater proportions of Fe and initially adsorbed P were released from ferrihydrite when compared with goethite. More P was released and Fe dissolved at pH 4.0 than pH 5.5 or 7.0 from both oxides. For ferrihydrite, the order of effectiveness of the organic ligands for P release at pH 4 was citrate (19% of the total initially adsorbed P) > malate (14%) > tartrate (5%)>> oxalate = malonate = succinate (0.3–1.2%). For Fe release at pH 4, the order was oxalate (18% of total oxide suspension Fe dissolved) ≈ citrate (17%) > malonate (13%) > malate (8%) > tartrate (5%) >> succinate (0.02%). Faster phosphate readsorption in the case of oxalate than citrate probably accounted for the low apparent release of P by oxalate in spite of its greater Fe dissolution. At the smaller adsorbed‐P concentration (1/4 of the adsorption maximum), the predominant mechanism of organic‐acid induced P release was ligand‐enhanced dissolution of the Fe oxide rather than ligand exchange. At 3/4 of the adsorption maximum, ligand exchange contributed to a greater extent to P release. Under low P‐fertility conditions, organic‐acid exudation would be more effective at increasing P availability in soils dominated by poorly crystalline than well‐crystalline Fe oxides.